Analisis Penerapan Key Audit Matters (KAM) Sesuai Dengan Standar Audit 701 terhadap Peningkatan Kualitas Audit: Literatur Review 2022-2024 - Wijayanti, Nanda Debi; Haryati, Tantina (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Key Audit Matters (KAM) is a very significant matter in auditing an entity's financial statements that are communicated by the auditor in the audit report. KAM is not a separate opinion or an indication that there is material misrepresentation, but the result of the auditor's professional discussion on the complexity of the audit. KAM focuses on crucial areas and material risks. Because KAM explains several things that are very crucial for the company, so not all audit report results apply KAM properly. This study examines the analysis related to the implementation of Key Audit Matters (KAM) in line with the 701 Audit Standard and its effect on the quality of the audit results produced. The methodology used includes a literature review, facilitated through the use of Google Scholar. The data obtained have undergone qualifications, covering 2022-2024, maintaining a thematic focus and coherent discourse with this study. Furthermore, this data is subject to analytical supervision. The findings of the investigation regarding the implementation of Key Audit Matters (KAM) in accordance with Audit Standard 701 reveal its impact on the quality of the audit results produced. The implementation of KAM has a beneficial effect on audit results, making it more informative and reliable for the decision-making process. KAM assists auditors in identifying issues that require disclosure in accordance with SA 701, thereby improving the transparency and communicative efficacy of audit reports for stakeholders. However, the disclosure of KAM also presents significant risks for companies related to the confidentiality of company data. Therefore, professional communication is needed in compiling and implementing KAM.